Laser Photobiomodulation in the acute inflammatory response of the calcaneal tendon injury in rats exposed to cigarette smoke - Naira Helena Bohrer Scherer; Antonio Marcos Vargas da Silva; Jessié Gutierres; Carolina Fantinel Veloso; Carlos Eduardo Pinfildi; Rafael Corrêa Gobbato (Universidade de São Paulo, 2019)
ABSTRACT Nicotine delays the healing process and increases the levels of myeloperoxidase (MPO), an enzyme that plays a key role in the production of reactive oxygen species during the inflammatory process. Laser Photobiomodulation (PBM) is one of the most used electrophysical agents in the treatment of the calcaneal tendon, however, its effects on MPO activity need to be further elucidated. This study aimed to evaluate the effects of laser PBM on MPO activity after inflicting an injury to the calcaneal tendon of rats exposed to cigarette smoke. Thirty-four male Wistar rats with 90 days of age were used. After 14 days of exposure to cigarette smoke, the animals were divided into three experimental groups: control group (CG, n=12), not submitted to injury or treatment; sham group (ShG, n=10), submitted to partial calcaneal tendon injury and laser PBM simulation; and laser PBM group (PBMG, n=12), submitted to partial calcaneal tendon lesion and treated with laser PBM within the first minute after injury. PBM decreased MPO activity levels in PBMG compared to ShG (CG: 1.38±0.69pg/ml; ShG: 3.78±1.09pg/ml; PBMG: 2.58±0.93pg/ml; p<0.005). In conclusion, applying laser PBM immediately after inflicting damage to the calcaneal tendon attenuates acute inflammatory activity in rats exposed to cigarette smoke.